The family tree - Peet, Mal (Edinburgh: Barrington Stoke, 2018)
When a man returns to his childhood home and visits the derelict tree house in which his father once chose to live, he recalls the past unravelling of his family, the unspoken strangeness of their lives, and the impact on his own adult life. Beautiful, sparse and insightful storytelling
Keywords: Young adult fiction